Phenotypic and histological analyses on the resistance of melon to Phelipanche aegyptiaca - Cao, Xiaolei; Xiao, Lifeng; Zhang, Lu; Chen, Meixiu; Bian, Pengxuan; Ma, Qianqian; Chen, Siyu; He, Quanlong; Ma, Xinli; Yao, Zhaoqun; Zhao, Sifeng (Frontiers in Plant Science, 2023)
Melon (Cucumis melo L.) is an economically important crop in Xinjiang, China, but its production is constrained by the parasitic plant Phelipanche aegyptiaca that attaches to the roots of many crops and causes severe stunting and loss of yield. Rhizotron, pot, and field experiments were employed to evaluate the resistance of 27 melon cultivars to P. aegyptiaca. Then, the resistant and susceptible cultivars were inoculated with P. aegyptiaca from six populations to assess their resistance stability and broad spectrum. Further microscopic and histological analyses were used to clarify the resistance phenotypes and histological structure. The results showed that Huangpi 9818 and KR1326 were more resistant to P. aegyptiaca compared to other cultivars in the rhizotron, pot, and field experiments. In addition, compared to the susceptible cultivar K1076, Huangpi 9818 and KR1326 showed broad-spectrum resistance to six P. aegyptiaca populations. These two resistant cultivars had lower P. aegyptiaca biomass and fewer and smaller P. aegyptiaca attachments on their roots compared to susceptible cultivar K1076. KR1326 (resistant) and K1076 (susceptible) were selected to further study resistance phenotypes and mechanisms. Germination-inducing activity of root exudates and microscopic analysis showed that the resistance in KR1326 was not related to low induction of P. aegyptiaca germination. The tubercles of parasite on KR1326 were observed slightly brown at 14 days after inoculation (DAI), the necrosis and arrest of parasite development occurred at 23 DAI. Histological analysis of necrosis tubercles showed that the endophyte of parasite had reached host central cylinder, connected with host xylem, and accumulation of secretions and callose were detected in neighbouring cells. We concluded that KR1326 is an important melon cultivar for P. aegyptiaca resistance that could be used to expand the genetic basis of cultivated muskmelon for resistance to the parasite.